Hybrid biological processes for the treatment of oily wastewater - Samal K.; Geed S.R.; Mohanty K. (My University, 2025)
The oil spillage in the marine environment is a combined result of industrial effluent discharge, waste soil burns, pipeline leakage, and drilling activities. Oil spillage is a mixture of wide range hydrocarbons that are released into the environment, which has an adverse effect on human beings as well as the aquatic life. The treatment of oil spillage has been great importance to save the marine environment. Several physicochemical techniques have been tested to treat oily contaminants but their application is limited due to its disadvantages. In past years, the biological methods have shown great potential to treat oily contaminants. The rate of degradation of oil spillage in biological processes is further improved using hybrid biological processes and targeted microbes. This chapter discusses the fundamental principles, mechanisms, and kinetics of the biological processes used for the treatment of oil spillage. Further, this chapter gives insight into the hybrid biological processes. © 2022 Elsevier Inc. All rights reserved.